The names they gave us - Lord, Emery (Bloomsbury, 2017)
When her perfectly planned summer of quality time with her parents, her serious boyfriend, and her Bible camp unravels and long-hidden family secrets emerge, Lucy must figure out what she is made of and what grace really means.